O črnogorski trilogiji Petra II. Petroviča - Njegoša - Osolnik, Vladimir (Jezik in slovstvo, 2014)
During the past decades of in-depth analysis of the literary texts of the Montenegrin poet and ecclesiastical and secular ruler of Montenegro, Radivoj Petrović (1813-1833), later known as Petar II Petrović Njegoš (1833-1851), two new realisations have gradually taken shape: firstly, the actual chronology of the creation of his so-called major literary works (The Ray of the Microcosm, The False Tsar Stephen the Little and The Mountain Wreath in 1845, 1846 and 1847 respectively), and secondly the trilogy as an intentional literary and ideological Montenegrin oeuvre or a planned authorial written record as the foundation of the specific Montenegrin national identity.
Keywords: Petrović-Njegoš, Petar, črnogorski vladika, 1813-1851; črnogorska književnost; epi; religiozni ep; filozofsko religiozni ep; črnogorski pisatelji; črnogorski vladika; trilogije